Legal Challenges in the Implementation of Electronic Data Interchange in Transport Documents - Časlav Pejović (Poredbeno Pomorsko Pravo, 1997)
EDI is emerging as a genuinely new means of transferring information, completely different from paper documents. For centuries, paper documents were the dominant means of communicating information, and even now, at the end of 2Oth century, they still keep this position. However, there is no doubt that in first decades of next century EDI will replace paper documents to become the dominant and, in the future probably exclusive means of communicating information, at least in business transactions. The existinglaws affecting commercial transactions do not provide a satisfactory environment to allow the use of EDI or other similar means of data communication. The traditional law contains various requirements that are obstructive to electronic commerce. The computer revolution has found many jurisdictions not prepared to deal with the electronic transfer of data. In addition, there is considerable lack of international uniformity in this area. (...)